Albert Shaw correspondence - Shaw, Albert, 1857-1947.
Photocopies of typewritten letters to Shaw from Warren G. Harding, Herbert Hoover, and Theodore Roosevelt. Also includes one letter from Shaw to Roosevelt.
Positive photocopies.
Editor and historian.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Harding, Warren G. -- 1865-1923 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; United States -- Politics and government -- 20th century; Editors; Historians